2014
DOI: 10.1088/1742-6596/524/1/012099
|View full text |Cite
|
Sign up to set email alerts
|

Rotor aerodynamic power limits at low tip speed ratio using CFD

Abstract: Abstract. When investigating limits of rotor aerodynamic models, the Betz limit serves as a solid marker of an upper limit which no model should be able to exceed. A century ago Joukowsky (1912) proposed a rotor aerodynamic model utilizing a rotating actuator disc with a constant circulation. This model has since then been the subject of much controversy as it predicts a power performance that for all tip speed ratios exceeds the Betz limit and which goes to infinity when the tip speed ratio goes to zero. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…He also considers optimal performance (maximizing the power at any λ) for smaller λ and compares several models in his Figure 6.14. Further studies of optimal performance include Mikkelsen et al (2014) who suggested that the wake at low λ may be subject to breakdown, and Vaz and Wood (2016) whose model did not lead to breakdown. The λ− dependence of the optimum power coefficient, C P , and thrust coefficient, C T , is still an open question because their theoretical foundation has not been investigated fully and the susceptibility to breakdown needs further consideration.…”
Section: Introductionmentioning
confidence: 99%
“…He also considers optimal performance (maximizing the power at any λ) for smaller λ and compares several models in his Figure 6.14. Further studies of optimal performance include Mikkelsen et al (2014) who suggested that the wake at low λ may be subject to breakdown, and Vaz and Wood (2016) whose model did not lead to breakdown. The λ− dependence of the optimum power coefficient, C P , and thrust coefficient, C T , is still an open question because their theoretical foundation has not been investigated fully and the susceptibility to breakdown needs further consideration.…”
Section: Introductionmentioning
confidence: 99%